2022
DOI: 10.1101/2022.01.31.478521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Classification Method Based on Dynamic Ensemble Selection and its Application to Predict Variance Patterns in HIV-1 Env

Abstract: Therapeutics that target the envelope glycoproteins (Envs) of human immunodeficiency virus type 1 (HIV-1) effectively reduce virus levels in patients. However, due to mutations, new Env variants are frequently generated, which may be resistant to the treatments. The appearance of such sequence variance at any Env position is seemingly random. A better understanding of the spatiotemporal patterns of variance across Env may lead to the development of new therapeutic strategies. We hypothesized that, at any time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…We recently examined the within-host patterns of amino acid variability in the envelope glycoproteins (Envs) of human immunodeficiency virus type 1 (HIV-1) 22 . We found that the variability at many positions of the CD4-binding site can be accurately estimated by the variability at adjacent positions on the three-dimensional structure of the protein.…”
Section: A High Volatility State and A High Volatility Environment In...mentioning
confidence: 99%
“…We recently examined the within-host patterns of amino acid variability in the envelope glycoproteins (Envs) of human immunodeficiency virus type 1 (HIV-1) 22 . We found that the variability at many positions of the CD4-binding site can be accurately estimated by the variability at adjacent positions on the three-dimensional structure of the protein.…”
Section: A High Volatility State and A High Volatility Environment In...mentioning
confidence: 99%